Mineralogical variation of the late stage mare basalts. Issue 10 (12th October 2016) - Zhang, Xunyu; Wu, Yunzhao; Ouyang, Ziyuan; Bugiolacchi, Roberto; Chen, Yuan; Zhang, Xiaomeng; Cai, Wei; Xu, Aoao; Tang, Zesheng
Abstract: The last major phases of lunar volcanism occurred mainly in Oceanus Procellarum and Mare Imbrium and produced spectrally unique medium‐ and high‐titanium basalts. The composition and distribution of these basalts provide a record of the late stage thermal evolution of the Moon. To study the spectral and mineralogical variations of the late stage mare basalts, 31 distinct units were mapped employing a range of remote sensing data. Their inferred mineralogical characteristics were studied by analyzing the spectral features of small, fresh craters derived from the Moon Mineralogy Mapper (M 3 ) data. The strongest olivine spectral signatures were found around Lichtenberg crater, while the units with the lowest olivine/pyroxene ratio occurred mainly in the southern Kepler crater and some local areas. In Oceanus Procellarum, the olivine/pyroxene ratio decreases progressively from the Lichtenberg crater to the southern units. The northern and southern units within Mare Imbrium have higher olivine/pyroxene ratios than the central ones. The inferred abundance of olivine appears to vary stratigraphically, with the younger flows being more olivine rich. However, the stratigraphically younger units around Euler crater in Mare Imbrium, which present as dark red hues in the integrated band depth image of M 3, were found to have lower olivine/pyroxene ratios than the units around Lichtenberg crater (shown as light red hues) in Oceanus Procellarum. It could be interpreted that the late stage mare basalts around Lichtenberg crater originated from a more olivine‐rich source than those around Euler crater. Key Point: This study mapped 31 units of the late stage mare basalts and analyzed the mineralogical variation among them